(untitled) (Research, Society and Development, 2024)
Introduction: PRF, a second generation autologous platelet concentration is obtained from the patient’s own blood and is widely used to accelerate soft and hard tissue healing. The PRF protocol is based on centrifuging 10 ml of the patient’s blood at 3,000 rpm for 10 min. The aim of the present study is to determine the effectiveness of fibrin-rich plasma (FRP) after intraalveolar application following surgical removal of mandibular third molars, based on signs and symptoms. Methodology: The research was a case report with a qualitative approach to analyze the efficacy of PRF after its application after mandibular third molar surgery, and an electronic search was performed in databases such as: Medline, Scielo, ScienceDirect. Articles published between the year 2017 to 2023, in English, Spanish and Portuguese language were used. Clinical case: A 22-year-old female patient came to the dental clinic for extraction of mandibular third molars with painful symptoms. The pieces 3.8 and 4.8 were extracted, using the PRF in piece 4.8 and piece 3.8 as a control. The response to pain, inflammation and healing was evaluated at 7, 15 days and one month. Conclusions: PRF acts as a biomaterial capable of accelerating the healing processes of soft tissues in the oral cavity, has the advantage of being low cost, reducing inflammation and pain.